ABNORMAL DIFFERENTIATION OF THE CHORION AND ITS RELEVANCE TO THE DEVELOPMENT OF THE CONCEPTUS - DD Farhud; H Sadighi ; M.R. Mohammad Hassani ; A. Samavat; R. Zakizadeh ; Z. Yazdani (Tehran University of Medical Sciences, 1996)
Thalassemias, because of climatic, geographic and ecological conditions, are the most common among the genetically endemic in Iran, especially m provinces adjacent to the Caspian Sea and the Persian Gulf. There are over 14,000 cases of thalassemia major reported in Iran. Data, collected by the Iranian Ministry of Health, and analyzed at the Department of Human Genetics, School of Public Health, Tehran University of Medical Sciences, showed relative distribution of 3194 patients referring for the iron chelating drug, disferal, in 24 provinces in Iran. 3304 cases were studied for sex and age groups. Higher percentages and sex ratios were observed in each age group and further clarified as the age increased. 3386 cases were considered for ABO and Rh blood groups. Significant high incidence of group 0 (41.228%) was followed by groups A (29.090%) and B (23.2 13%), and group AB with the lowest (6.467%). A significant low incidence of Rh negative was also observed (6.852%).